Effect of Intake Manifold Porting and Polishing and Throttle Body Venturi Diameter Modification on Motorcycle Performance - Anbia, Gun Gun; Arwati, I Gusti Ayu (Universitas Mercu Buana, 2024)
This study aims to investigate the effect of intake manifold and throttle body modifications on the performance of a Yamaha Mio M3 125cc motorcycle engine. A two-level factorial experimental design with two factors was employed: intake manifold diameter (27 mm and 30 mm) and throttle body diameter (26 mm and 28 mm). Data were collected using a dyno test and analyzed using statistical methods. The results revealed that intake manifold and throttle body modifications significantly influenced the performance of the Yamaha Mio M3 125cc motorcycle engine. The combination of a 27 mm intake manifold and a 28 mm throttle body produced the highest torque of 23.1 Nm at 2,058 RPM, while the combination of a 27 mm intake manifold and a 26 mm throttle body generated the highest power of 11.2 HP at 7,155 RPM. These modifications resulted in a 10.53% increase in torque and a 16.67% increase in power compared to the standard configuration. Modifying the intake manifold and throttle body can enhance the performance of the Yamaha Mio M3 125cc motorcycle engine. Keywords: Intake manifold modification, Throttle body modification, Engine performance, Yamaha Mio M3 125cc